2019
DOI: 10.1007/s42452-019-1405-4
|View full text |Cite
|
Sign up to set email alerts
|

Integrated GIS-based modelling approach for irrigation water quality suitability zonation in parts of Satluj River Basin, Bist Doab region, North India

Abstract: The groundwater is the main source for irrigation and other purposes in the alluvial plains of Punjab. The poor irrigational water quality affects the soil quality which interrupts the growth of plants impacting the agricultural production and can cause risk to human health, and thus, it is important to evaluate the water quality for irrigation uses in the agrarian regions. An integrated GIS-based modelling approach along with conventional water quality indices such as sodium adsorption ratio, per cent sodium,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Furthermore, the aforementioned techniques to assess the water quality, Water Quality Indices (WQIs) are used to determine the quality of water, which present a useful interpretation of the quality of water used for irrigation. The individual water quality parameter is not adequate to estimate the validation of water for irrigation because it can be restrictive and may often produce inadequate performance in the evaluation [23]. The weighted score of each variable was used by several other studies to suggest a water quality index [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the aforementioned techniques to assess the water quality, Water Quality Indices (WQIs) are used to determine the quality of water, which present a useful interpretation of the quality of water used for irrigation. The individual water quality parameter is not adequate to estimate the validation of water for irrigation because it can be restrictive and may often produce inadequate performance in the evaluation [23]. The weighted score of each variable was used by several other studies to suggest a water quality index [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, different weight rankings (e.g. suitable; moderately suitable; and unsuitable) (Doneen 1964;Todd 1980;Wilcox 1955;Singh et al 2019). Spatial distribution maps were then generated for each parameter by integrating the inverse distance Weighting (IDW) technique and simple kriging (SK).…”
Section: Gis-based Irrigational Water Quality Zonationmentioning
confidence: 99%
“…All thee input parameters were assigned an equal weightage of 1 (Table 2). As proposed by Singh et al (2019), there is an equal importance for all the irrigation water quality parameters in irrigation water quality assessment. However, an observation of the results of the irrigation water quality (Table 2) revealed that some variables (e.g.…”
Section: Gis-based Irrigational Water Quality Zonationmentioning
confidence: 99%
See 2 more Smart Citations